Determinants of Distribution Patterns and Management Needs in a Critically Endangered Lion Panthera leo Population - Henschel, Philipp; Petracca, Lisanne S.; Hunter, Luke T. B.; Kiki, Martial; Sewadé, Clement; Tehou, Aristide; Robinson, Hugh S. (Frontiers in Ecology and Evolution, 2016)
The lion Panthera leo is Critically Endangered in West Africa and is known to occupy only four protected areas within the region. The largest population persists in the trans-boundary W-Arly-Pendjari (WAP) ecosystem, in the border region of Benin, Burkina Faso, and Niger. WAP harbors an estimated 350 individuals, or 90% of West Africa’s lions. We modeled lion occupancy across WAP using systematic, vehicle-based spoor counts to assess how landscape variables related to biotic factors, management and human impact influence lion distribution across WAP. We surveyed 1110 km of roads across WAP in 2012, obtaining 79 lion detections in 32 of our 167 15 x 15 km sampling units (naïve occupancy = 0.41). Overall occupancy (Ψ) was 0.71 (95% SE = 0.56-0.83) when accounting for imperfect detection (p = 0.22, 95% SE = 0.18-0.27). The best predictors of lion occupancy were numbers of permanent protected area staff and mean monthly dry season precipitation. Model-averaged estimates suggest greatest lion occupancy in the Arly and Pendjari management blocks, with lowest occupancy in the tri-national W National Park. Our results suggest that lions in WAP are equally limited by management and biotic factors, and demonstrate how unevenly distributed protection effort limits the distribution of an apex predator across a protected landscape. We strongly recommend increased funding and better protection to increase lion occupancy in WAP, most urgently in the W National Park.